Palinología del Cretácico Inferior de la sección de Montoria-La Mina (Cuenca Vasco-Cantábrica, Españ - García-blanco, Víctor E.; Barrón, Eduardo; Comas-rengifo, María José (Coloquios de Paleontología, 2004)
The Lower Cretaceous Montoria-La Mina section is located in the extreme southern part of the BasqueCantabrian Basin (Spain). The succession might be included into the Escucha Formation and contains siltstones and clays with interbedded deltaic lignite and sandstone rocks. The palynological analysis of these rocks shows well preserved miospore assemblages with significant numbers of specimens in eight of the twelve analysed horizons. A diverse flora composed of forty four vascular cryptogams and twenty eight fanerogams are identified, included in the divisions Bryophyta, Lycophyta, Pteridophyta, Pteridospermophyta, Coniferophyta, Cycadophyta/Ginkgophyta, Gnetophyta and Magnoliophyta. The palynological assemblages are dominated by anemophilous pollen grains of Corollina obidosensis and Inaperturopollenites dubius, as well as psilate spores of Cyathidites australis, which suggest warm and dry climatic conditions. The occurrence of pollen grains of ancient angiosperms is significant in the studied assemblages. They were identified as small-sized, reticulate and generally collumelate miospores. Inaperturate, operculate, monosulcate and trichotomosulcate forms attributed to the Pre-Afropollis, Clavatipollenites, Liliacidites, Retimonocolpites and Retimonoporites pollen groups are described. The appearance of these palynological groups are compared to those in the lower part of Zone I of Potomac Group (Maryland, USA) and in the Lower Cretaceous of Israel.